The Routledge international handbook of research on writing - Horowitz, Rosalind (Routledge handbooks in communication studies, 2023)
"This scholarly research handbook aggregates the broad-ranging, interdisciplinary, multidimensional strands of writing research from scholars worldwide and brings them together into a common intellectual space. Now in its second edition, the Handbook inaugurates a wide scope of international research advancement, with attention to writing at all levels of schooling and in all life situations. It provides advanced surveys of scholarship on the histories of world and child writing and literacy; interconnections between writing, reading, and speech; digital writing; writing in communities; writing in the sciences and engineering; writing instruction and assessment; and writing and disability. A section on International measures for assessment of writing is a new addition to this compendium of research. This volume serves as a comprehensive resource for scholars, graduate students, and advanced undergraduates in writing studies and rhetoric, composition, creative expression, education, and literacy studies"--